An auction approach for resource allocation in cognitive radio networks - Liu, Chenglong (2016)
We aim to solve the shortage of radio frequency spectrum via better practical utilisation and distribution of existing spectrum through an auction-based approach system where primary users (government licensed entities) leash unused frequency bands to secondary users (non-government licensed entities) .In an ideal dynamic cognitive radio network, primary users (PU) can share and rent their own licensed frequency spectrum to secondary users (SU) without restriction. Therefore we utilised an auction-based dynamic cognitive radio network experimental model involving multiple PUs and SUs in an oligopoly virtual market [10] where PU and SU are both profit-orientated and non-cooperative. This experiment adopts a Hackner utility function [3] and Matlab programming tools to find the demands for the radio spectrum from each SU. In an ideal situation, resources are allocated efficiently to the parties that value them the most securing revenue in the process. From the results of the selected optimal scenario know as Nash equilibrium in each stage of the dynamic auction game, we explore the feasibility and various limitations of this proposed experiment.